2012
DOI: 10.4070/kcj.2012.42.3.205
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Echo-A Simple Diagnostic Tool for a Coronary Artery Fistula

Abstract: Coronary artery fistulas have been diagnosed with aortography, coronary angiography, and coronary computed tomography (CT). A large fistula can be occasionally found as a mass lesion on echocardiography but cannot be easily confirmed. Here, we report a new diagnostic approach to coronary artery fistulas using a contrast agent and transthoracic echocardiography. Transthoracic echocardiography of a 46-year-old female suffering from dyspnea revealed suspicious small turbulent flow in the main pulmonary artery. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Echocardiographic evaluation, both TTE and TEE, is limited by fields of view and operator dependency, but can delineate CAF anatomy, and analyze CAF associated hemodynamic and physiologic changes while avoiding radiation exposure [19,22]. Use of micro-bubble contrast can enhance echocardiography by more precisely determining the extent and location of the CAF, but has diminished utility in CAFs with distal arterial origins [19,23,24]. Current guidelines refer to the use of surveillance echocardiography every 3–5 years for follow up of patients with small and asymptomatic CAF to monitor for fistula progression and terminating chamber enlargement [17].…”
Section: Discussionmentioning
confidence: 99%
“…Echocardiographic evaluation, both TTE and TEE, is limited by fields of view and operator dependency, but can delineate CAF anatomy, and analyze CAF associated hemodynamic and physiologic changes while avoiding radiation exposure [19,22]. Use of micro-bubble contrast can enhance echocardiography by more precisely determining the extent and location of the CAF, but has diminished utility in CAFs with distal arterial origins [19,23,24]. Current guidelines refer to the use of surveillance echocardiography every 3–5 years for follow up of patients with small and asymptomatic CAF to monitor for fistula progression and terminating chamber enlargement [17].…”
Section: Discussionmentioning
confidence: 99%
“…One study reported the diagnosis of a small coronary-pulmonary fistula (CPF) by echocardiography in asymptomatic dizygotic twin infant brothers[ 31 ], suggesting a possible genetic cause of CAFs. Invasive CAG is considered the gold standard for the detection and diagnosis of congenital CAFs; however, non-invasive imaging techniques such as contrast echocardiography[ 34 ], 2D and color Doppler echocardiography, cardiovascular MRI and CTCA provide valuable complementary data for the visualization of fistula components (origin, pathway and termination sites) that are not visible on the CAG[ 20 , 35 - 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of echocardiography contrast for the localization of coronary-cameral fistulas has been previously described. 13 , 14 It is important to note that this is an off-label use of echocardiography contrast and that intra-arterial injection is listed as contraindicated on the contrast product label. This simple diagnostic procedure confirmed the coronary-cameral fistula location and excluded a life-threatening complication of infarct angioplasty.…”
Section: Discussionmentioning
confidence: 99%